Integrating systemic immune-inflammation index, fibrinogen, and T-SPOT.TB for precision distinction of active pulmonary tuberculosis in the era of mycobacterial disease research - Yu, Zhikang; Shang, Zifang; Huang, Qingyan; Wen, Feiqiu; Patil, Sandip (Frontiers in Microbiology, 2024)
Background: The clinical challenge of differentiating suspected tuberculosis with positive T-SPOT.TB results persist. This study aims to investigate the utility of the Systemic Immune-Inflammation Index (SII), Fibrinogen, and T-SPOT.TB in distinguishing between active pulmonary tuberculosis (PTB) and non-tuberculous lung diseases. Methods: A retrospective analysis included 1327 cases of active PTB with positive T-SPOT.TB results and 703 cases of non-tuberculous lung diseases from May 2016 to December 2020 at Meizhou People's Hospital.These were designated as the case group and the control group, respectively. The detection indicators of T-SPOT.TB: Early Secreted Antigenic Target 6 (ESAT-6), Culture Filtrate Protein 10 (CFP-10), as well as SII and Fibrinogen levels-were compared and analyzed for association and joint diagnostic value between the two groups. Results: The case group showed higher values of ESAT-6, CFP-10, SII, and Fibrinogen compared to the control group (all P < 0.001). In the case group, SII and Fibrinogen did not correlate with ESAT-6 and CFP-10 (|rs| all < 0.3) but were positively correlated with C-reactive protein (CRP) (rs all > 0.3). SII and Fibrinogen values in smear-positive pulmonary tuberculosis were higher than in smearnegative cases (all P < 0.05). The optimal diagnostic thresholds for ESAT-6, CFP-10, SII, and Fibrinogen in differentiating between active PTB and non-tuberculous lung diseases were 21.50 SFCs/10 6 PBMC, 22.50 SFCs/10 6 PBMC, 2128.32, and 5.02 g/l, respectively.Regression logistic analysis showed that ESAT-6<21.5 (OR: 1.637, 95% CI: 1.311-2.043, P<0.001), CFP-10 <22.5 (OR: 3.918, 95% CI: 3.138-4.892, P=0.025), SII <2128.32 (OR: 0.763, 95% CI: 0.603-0.967, P<0.001), and FIB<5.02 (OR: 2.287, 95% CI: 1.865-2.806, P<0.001) were independent risk factors for active PTB. The specificity for ESAT-6+CFP-10, ESAT-6+CFP-10+SII, ESAT-6+CFP-10+FIB, and ESAT-6+CFP-10+SII+FIB was 82.5%, 83.2%, 95.8%, and 80.1%, respectively, while sensitivity was 52.6%, 53.0%, 55.8%, and 44.7%, and positive predictive values were 85.0%, 85.6%, 84.1%, and 89.6%, respectively.: SII and Fibrinogen are positively correlated with the degree of tuberculosis inflammation and the bacterial load of Mycobacterium tuberculosis. The combined detection of SII, Fibrinogen, and T-SPOT.TB is significant in distinguishing between active PTB with positive T-SPOT.TB results and non-tuberculous lung diseases.